Better healthcare: Exploring business intelligence for healthier Malaysian rural dwellers - Ahmad, Azizah; Muraina, Ishola Dada; Abd Razak, Rafidah; Abdullah, Mohd Syazwan (2013)
Healthcare in the rural areas have been encountering decision making issues which are due to the lack of maximising the use of their historical data.It is a general believe that many of healthcare data together with strong analytics by business intelligence brings about proposition for attainment of community healthcare success.This study intends to explore and analyse the phases leading to the business intelligence requirements for strategic decision in healthcare organisation in rural healthcare in Malaysia.Thus, goal-oriented approach and Requirements Management Control methodology are employed, leading to the requirement analysis model for Malaysian rural healthcare.